HYPERTEXT OF A. A. FET'S POEM «SOUTHERN NIGHT IN THE HAYSTACK …» (Филологический класс, 2018)
The article discusses the possibility of expanding the semantic field of interpretations of A. Fet' poem «Southern Night In the Haystack…». The purpose of the work is to substantiate the potential for interpretation of A.A. Fet's poem and to treat it as a reflective poem, not a philosophical one exploring the transcendental transition into the unknown. It is also important to determine the place of the poem in the poetic tradition of thinking about the relationship of the subject and the lyrical «starry abyss» as metaphors of the scope of knowledge. Based on S. Bocharov's ideas about the existence of a common space of literary works, M. Khrapchenko's view about the potential existence of all the meanings in the literary text that are extracted by different generations of readers and a relatively new methodology of hypertext, the paper substantiates the possibility of a new interpretation of A. A. Fet's poem. This approach and the results of the work seem to be productive for practice of modern school literary education as an alternative to the method of «instructive understanding» of classical texts, as they allow students to demonstrate one of the ways to comprehend the meaning of the literary text as a sense-generating mechanism that continues its life in culture, entering into numerous figurative and associative links with other texts.